How do you find the derivative of (x-3) /( 2x+1)x32x+1?

1 Answer
Jun 16, 2018

d/dx ( (x-3)/(2x+1)) = 7/(2x+1)^2ddx(x32x+1)=7(2x+1)2

Explanation:

Using the quotient rule:

d/dx ( (x-3)/(2x+1)) = ( (2x+1) d/dx (x-3) - (x-3)d/dx (2x+1))/(2x+1)^2ddx(x32x+1)=(2x+1)ddx(x3)(x3)ddx(2x+1)(2x+1)2

d/dx ( (x-3)/(2x+1)) = ( (2x+1) - 2(x-3))/(2x+1)^2ddx(x32x+1)=(2x+1)2(x3)(2x+1)2

d/dx ( (x-3)/(2x+1)) = ( 2x+1- 2x+6)/(2x+1)^2ddx(x32x+1)=2x+12x+6(2x+1)2

d/dx ( (x-3)/(2x+1)) = 7/(2x+1)^2ddx(x32x+1)=7(2x+1)2